2015
DOI: 10.1038/sc.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor improvement of spinal cord-injured rats through treadmill training by forced plantar placement of hind paws

Abstract: Study design: Experimental training model of rats with spinal cord injury (SCI).Setting: Osaka, Japan Objective: To investigate the effect of forced treadmill training by plantar placement (PP), as compared with dorsal placement (DP), of the dorsal paws on the locomotor behaviors of spinal cord-injured rats. Methods: The spinal cord was contusion-injured at the thoracic level. Rats were divided into three groups: forced training involving stepping by PP and DP and non-forced training/assistance (nT). Training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, there are no other reports of treadmill training worsening BBB scores in rats after SCI. On the contrary, no improvements or early improvements to BBB scores following treadmill training have been reported by multiple teams (Fouad et al, 2000;Hayashibe et al, 2016;Heng and de Leon, 2009;Multon et al, 2003). Specifically, quadrupedal training did not affect BBB scores above 'self-training' (Fouad et al, 2000), whereas bipedal, hindlimb treadmill training was shown to improve BBB scores, in some cases with an improvement of more than eight points (Hayashibe et al, 2016;Multon et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, there are no other reports of treadmill training worsening BBB scores in rats after SCI. On the contrary, no improvements or early improvements to BBB scores following treadmill training have been reported by multiple teams (Fouad et al, 2000;Hayashibe et al, 2016;Heng and de Leon, 2009;Multon et al, 2003). Specifically, quadrupedal training did not affect BBB scores above 'self-training' (Fouad et al, 2000), whereas bipedal, hindlimb treadmill training was shown to improve BBB scores, in some cases with an improvement of more than eight points (Hayashibe et al, 2016;Multon et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Exercise therapy (such as treadmill training, TT) is a simple and easy method in SCI rehabilitation that promotes the overall functional recovery in animals and patients with SCI via reduced syringomyelia area and formation of glial scar, promoting axonal and synaptic regeneration, and neural circuit reconstruction [6][7][8][9][10]. The above effects may be related to the increased expression of neurotrophic factors (NTs), such as brain-derived neurotrophic factor (BDNF) after exercise training in animals or individuals with SCI [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The plantar surface of the hind‐paw was stained with red ink and forepaw with blue ink and mice were made to walk on a strip of white paper fixed on a wooden beam. Stride length (SL) and stride width (SW) were measured for at least three consecutive (left and right steps) footprints per animal after SCI at 1, 7, and 14 days, as previously described …”
Section: Methodsmentioning
confidence: 99%